Potential areas for design and its implementation to enable the future viability of weaving practices in northern Thailand - Disaya Chudasri (2020)
© 2020 Chudasri, Walker, and Evans. This research paper examines traditional chok weaving in Northern Thailand to determine if and how design can contribute to its future viability. Research was conducted through extensive fieldwork. First, we describe traditional chok weaving and new developments in maintaining cultural significance. In addition, two distinct approaches to sustainability are identified: sustaining traditional practices of making textile products, and sustaining the social-cultural practices of product use. This paper also lays out potential areas for design contributions, and the framework of the four recommended design contributions is generated. These include design and production development, product design and development, design in relation to marketing and sales, and design to support the transfer of weaving expertise between generations. Project implementation with the weaving communities of the Long district is presented, producing tangible results, including a booklet and a card game of the traditional textile patterns for the weaving communities and interested people, and a repository of information, which the research group created for sharing information within the group.